Analisis Etika Komunikasi dalam Interaksi Guru dan Murid di Kelas - Kholizah, Nur Alfiana; Sani, Dinda Aulia; Munawwarah, Tarisa; Marpaung, Syafri Fadillah (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Based on research, communication ethics in interactions between teachers and students is very necessary because it greatly influences their behavior. To become teachers who are expected to fulfill the tasks given to us, we must surrender to God Almighty. Apart from that, the communication relationship between teachers and students is also a factor that influences the success of Islamic teaching. Ethics is also a dimension that deserves attention. Ethics gets attention because ethics is the core of educational goals. Ethics are rules, norms, rules or procedures that are often used as guidelines or principles for someone to carry out actions and behavior that are very important for life around us, because they apply to our daily behavior. Ethics guides a person or group in behaving and acting. As educators, teachers must be able to set an example in ethics and communication. To be successful in learning, teachers must provide students with an approach appropriate to their situation, which is important.